Evaluating the Influence of 3D-Printing Parameters on Acoustic Material Properties - Jäger, Axel; Johannesmann, Sarah; Claes, Leander; Webersen, Manuel; Henning, Bernd; Kupnik, Mario (2017 IEEE IUS~Proceedings)

Inverser Ansatz zur akustischen Charakterisierung plattenförmiger Materialproben - Johannesmann, Sarah; Claes, Leander; Webersen, Manuel; Henning, Bernd (Fortschritte der Akustik - DAGA 2017)

Material parameter determination of a piezoelectric disc with triple-ring-electrodes for increased sensitivity - Jurgelucks, Benjamin; Feldmann, Nadine; Claes, Leander; Henning, Bernd; Walther, Andrea (Proceedings of Meetings on Acoustics)

Ultrasonic measurements in the characterization of viscoelasticity and aging of polymers - Bause, Fabian; Claes, Leander; Webersen, Manuel; Henning, Bernd (PROCEEDINGS -- AMA Conferences 2017)

Determining fractional Zener model parameters from low frequency DMA measurements - Feldmann, Nadine; Bause, Fabian; Henning, Bernd (Proceedings – AMA Conferences 2017)

Spektrale Verfahren zur Bestimmung der akustischen Absorption in fluiden Medien - Claes, Leander; Feldmann, Nadine; Henning, Bernd

Start-up factory Ghana: Creating an enabling environment for the dissemination of renewable energies - Klaus, Tobias; Nkrumah, I.; Donkor, M.K.E; Tamakloe, R.Y.; Ampong, F.K.; Krauter, Stefan (Proceedings of the ISES Solar World Congress 2017)

Minimizing storage costs by substituting centralized electrical storage by thermal storage at the end user, also suppling balancing power for grid operation - Krauter, Stefan; Prior, Dirk (Energy Procedia)
Many processes in industrial and domestic applications require heating or cooling at certain steps of a process. Even if the process itself cannot be shifted towards periods of high PV output (which would be favorable), the heating and cooling necessities can be carried out via an inexpensive thermal storage instead of a costly electrical storage. Examples are: distillation units, washing machines, dishwashers, coolers, freezers. The resulting “shiftability” of power consumption can be a business model by offering that availability of load dispatching on the balancing power market. An example using PCM as cooling storage for refrigerators that has been investigated: A focus of this paper is the use of that load shifting ability to provide balancing power. Another emphasis is on the protection of individual consumer data: To keep the state of use of each individual consumer (actually: interactive consumer or “prosumer”) anonymous, but still performing the sales of balancing power, the orders for load-dispatching can be transmitted via transmitted via a regional, non-individual broadcasting message within the GSM network. Demonstrating DSMs capacities, abilities and limits concerning domestic applications is an important task to prepare large-scale implementation and to convince stakeholders. To reaching that goal, several realistic DSM scenarios for cooling applications and freezers have been developed with the prerequisite that DSM activities are supposed to be without comfort losses and without restrictions for consumers while the limits for lower and upper temperature for food are maintained.
Keywords: DSM; load management; load shifting; PCM; thermal storage; balancing power

Performance of MERRA2 Data Compared to Floating LiDAR - Bendfeld, Jörg; Balluff, Stefan; Wübbeke, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2017)

Short-term wind speed and power prediction for offshore wind farms using neural networks - Bendfeld, Jörg; Balluff, Stefan; Krüger, J.; Krauter, Stefan (Proceedings of the DEWEK 2017)

Update on rankings of conversion efficiencies and energy yield of micro-inverters, including inverters for two PV modules - Bendfeld, Jörg; Krauter, Stefan (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017, S. 1477–1481)

Long-term performance of PV micro-inverters - Bendfeld, Jörg; Krauter, Stefan (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017, S. 1836–1840)

Advanced PV Module Hot Spot Characterisation - Krauter, Stefan; Wendlandt, S.; Süthoff, L.; Berendes, S.; Teubner, J.; Podlowski, L.; Berghold, J.; Grunow, Paul (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017)

Comparison of Conversion Efficiencies and Energy Yields of Micro-Inverters for Photovoltaic Modules - Krauter, Stefan (VDE-Proceedings of NEIS 2017 – Conference on Sustainable Energy Supply and Energy Storage Systems by IEEE-PES. Hamburg (Deutschland), 21.–22. September, 2017.)

Smart Charging Management System of Plugged-in EVs for Optimal Operation of Future Power Systems. - Krauter, Stefan; Ameli, Ali (VDE-Proceedings of NEIS 2017 – Conference on Sustainable Energy Supply and Energy Storage Systems by IEEE-PES. Hamburg (Deutschland), 21.–22. September, 2017.)

Minimizing storage costs: Simple and effective methods to match PV with grid load, including shift of holiday period - Krauter, Stefan (Proceedings of the 11th International Conference for Renewable Energy Storage, 14-16 March 2017, Düsseldorf, Germany.)

Introduction of an Advanced Method for Testing of Battery Charge Controllers for Off-Grid PV Systems - Khatibi, Arash; Bendfeld, Jörg; Bermpohl, Wolfgang; Krauter, Stefan (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017)

Testing and Analysis of Battery Charge Controllers for Off-Grid PV Systems - Khatibi, Arash; Bendfeld, Jörg; Bermpohl, Wolfgang; Krauter, Stefan (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017)

Directional Emission from Dielectric Leaky-Wave Nanoantennas - Peter, Manuel; Hildebrandt, Andre; Schlickriede, Christian; Gharib, Kimia; Zentgraf, Thomas; Förstner, Jens; Linden, Stefan (Nano Letters)
Keywords: tet_topic_opticalantenna

A Study on Transfer Learning for Acoustic Event Detection in a Real Life Scenario - Arora, Prerna; Haeb-Umbach, Reinhold (IEEE 19th International Workshop on Multimedia Signal Processing (MMSP))
In this work, we address the limited availability of large annotated databases for real-life audio event detection by utilizing the concept of transfer learning. This technique aims to transfer knowledge from a source domain to a target domain, even if source and target have different feature distributions and label sets. We hypothesize that all acoustic events share the same inventory of basic acoustic building blocks and differ only in the temporal order of these acoustic units. We then construct a deep neural network with convolutional layers for extracting the acoustic units and a recurrent layer for capturing the temporal order. Under the above hypothesis, transfer learning from a source to a target domain with a different acoustic event inventory is realized by transferring the convolutional layers from the source to the target domain. The recurrent layer is, however, learnt directly from the target domain. Experiments on the transfer from a synthetic source database to the reallife target database of DCASE 2016 demonstrate that transfer learning leads to improved detection performance on average. However, the successful transfer to detect events which are very different from what was seen in the source domain, could not be verified.